please tell me the answer ✌️
![m - \frac{m - 1}{2 } \: = 1 - \frac{m - 2}{3} m - \frac{m - 1}{2 } \: = 1 - \frac{m - 2}{3}](https://tex.z-dn.net/?f=m+-+%5Cfrac%7Bm+-+1%7D%7B2+%7D+%5C%3A+%3D+1+-+%5Cfrac%7Bm+-+2%7D%7B3%7D+)
Answers
Answered by
1
Answer:
m=1
Step-by-step explanation:
(2m-m-1)/2=(3-m-2)/3
(m-1)/2 = (1-m)/3
3(m-1)=2(1-m)
3m-3=2-2m
3m+2m=2+3
5m=5
m=5/5
m=1
I HOPE YOU UNDERSTOOD THE QUESTION
Similar questions
English,
4 months ago
Math,
4 months ago
English,
4 months ago
English,
9 months ago
Math,
9 months ago
Accountancy,
1 year ago
Political Science,
1 year ago